AKTIVITAS FISIK REMAJA PADA MASA PANDEMI COVID-19 - Joyeti Darni; Retno Wahyuningsih; Lalu Khairul Abdi; Irianto Irianto (Jurnal Gizi Prima (Prime Nutrition Journal), 2021)
Background : The status of the Covid-19 pandemic has an impact on daily activities, the existence of social restriction policies has resulted in more people staying at home and has an impact on physical fitness. Adolescents’' physical activity has been related to activities at school, because schools were closed by the government during the Covid-19 pandemic, adolescents did a lot of activities in a sitting position such as studying online, playing online games, reading, watching television / cellphones. Behavior at home alone will be dangerous if it is not accompanied by active physical activity. This study aims to look at the description of physical activity during the Covid-19 pandemic.Methods : The research design used a cross sectional study, with adolescent respondents in the city of Mataram. Respondents were taken by random sampling and were willing to fill out informed consent. Physical activity questionnaire related to activities during the pandemic, frequency of sitting/lying down, frequency of standing/walking, frequency of lifting heavy weights, exercise habits, type of exercise, frequency of exercise, duration of exercise time, behavior of watching TV/mobile, length of time watching TV/mobile, habits cycling. Data were analyzed based on gender differences by univariate test, and using Chi Square test on physical activity.Results : Adolescent girls in this study were 85.14%, aged 19 years were 45.9%, and nutritional status was 5.4% underweight and 8.1% overweight. The results of the research showed that 90.5% of female adolescent girls were active at home, 54% of girls were sitting/lying down, while 63.6% of boys were standing/walking. The activity of lifting heavy weights is rarely carried out by teenage boys at 54.5%. Exercise habits were carried out by 90.9% male adolescents with 18.2% exercising 4-6 times/week, with a duration of 30 -60 minutes as much as 36.4%. Adolescent girls never cycled during the pandemic as much as 50.8%.Latar Belakang : Status pandemi Covid-19 berdampak terhadap aktivitas sehari-hari, adanya kebijakan kebijakan pembatasan sosial mengakibatkan masyarakat lebih banyak berdiam di rumah saja dan berdampak pada kebugaran fisik. Aktivitas fisik remaja selama ini berhubungan dengan aktivitas di sekolah, karena sekolah diliburkan oleh pemerintah selama pandemi Covid-19, remaja banyak melakukan kegiatan dalam posisi duduk seperti belajar online, bermain game online, membaca, menonton televisi / Hp. Perilaku dirumah saja akan berbahaya jika tidak dibarengi dengan aktivitas fisik yang aktif. Penelitian ini bertujuan untuk melihat gambaran aktivitas fisik selama pandemi Covid-19.Metode : Desain penelitian menggunakan cross sectional study, dengan responden remaja di Kota Mataram. Responden diambil secara random sampling dan bersedia mengisi informed consent. Kuesioner aktivitas fisik terkait aktivitas selama pandemi, frekuensi duduk/berbaring, frekuensi berdiri/berjalan, frekuensi mengangkat beban berat, kebiasaan olahraga, jenis olahraga, frekuensi olahraga, durasi waktu olahraga, perilaku nonton TV/Hp, lama waktu nonton TV/Hp, kebiasaan bersepeda. Data dianalisis berdasarkan perbedaan jenis kelamin secara uji univariate, dan menggunakan uji Chi Square terhadap aktifitas fisik. Hasil : Remaja perempuan pada penelitian ini sebanyak 85,14%, yang berumur 19 tahun sebanyak 45,9%, dan status gizi kurus berat 5,4% serta gemuk berat 8,1%. Hasil penelitian aktivitas fisik 90,5% remaja perempuan beraktivitas dirumah saja, aktivitas duduk/berbaring sering dilakukan remaja perempuan sebanyak 54%, sedangkan aktivitas berdiri/berjalan sering dilakukan oleh remaja laki-laki 63,6%. Aktivitas mengangkat beban berat jarang dilakukan remaja laki-laki sebesar 54,5%. Kebiasaan olahraga dilakukan oleh 90,9% remaja laki-laki dengan 18,2% berolahraga sebanyak 4-6 kali/minggu, dengan durasi 30 -60 menit sebanyak 36,4%. Remaja perempuan tidak pernah bersepeda selama pandemi sebanyak 50,8%.